General practitioners' satisfaction with and attitudes to out-of-hours services - Wesseling Geertjan; Voss Gemma BWE; Nieman Fred HM; van Uden Caro JT; Winkens Ron AG; Crebolder Harry FJM (BMC Health Services Research, 2005)
Abstract Background In recent years, Dutch general practitioner (GP) out-of-hours service has been reorganised into large-scale GP cooperatives. Until now little is known about GPs' experiences with working at these cooperatives for out-of-hours care. The purpose of this study is to gain insight into GPs' satisfaction with working at GP cooperatives for out-of-hours care in separated and integrated cooperatives. Methods A GP cooperative separate from the hospital Accident and Emergency (A&E) department, and a GP cooperative integrated within the A&E department of another hospital. Both cooperatives are situated in adjacent geographic regions in the South of the Netherlands. One hundred GPs were interviewed by telephone; fifty GPs working at the separated GP cooperative and fifty GPs from the integrated GP cooperative. Opinions on different aspects of GP cooperatives for out-of-hours care were measured, and regression analysis was performed to investigate if these could be related to GP satisfaction with out-of-hours care organisation. Results GPs from the separated model were more satisfied with the organisation of out-of-hours care than GPs from the integrated model (70 vs. 60 on a scale score from 0 to 100; P = 0.020). Satisfaction about out-of-hours care organisation was related to opinions on workload, guarantee of gatekeeper function, and attitude towards out-of-hours care as being an essential part of general practice. Cooperation with medical specialists was much more appreciated at the integrated model (77 vs. 48; P < 0.001) versus the separated model. Conclusion GPs in this study appear to be generally satisfied with the organisation of GP cooperatives for out-of-hours care. Furthermore, GPs working at the separated cooperative seem to be more satisfied compared to GPs working at the integrated cooperative.